The assessment of Danau Kota Lake water quality using chemometrics approach - Hafizan, Juahir; Azimah, Ismail; Mahadzirah, Mohamad; Adiana, Ghazali; Hamzah, F.M; Sudianto, S; Mohd Lasim, M.L; Shahriz, M.A (2019)
Danau Kota Lake is public attraction area, located in the middle area of Kuala Lumpur. An excessive count of visitors visiting the lake has weakening the lake water quality. The present study was driven to evaluate the lake water quality for environmental conservation. Some water quality and metals data were in-situ measured whereas some were collected for laboratory analysis. BOD, OG, AN and TC are identified as major pollutants towards Danau Kota Lake water quality. The decreasing concentration of DO and increasing of turbidity towards the deeper lake water column has been deteriorated the living water communities and caused hypoxic condition in the bottom water of Danau Kota Lake. Spatial variation of metals in the lake sediment has evidenced the accumulation of metals in the middle part of the lake area due to the sedimentation process. Based on PCA, the possible pollutant sources for this lake are the organic pollutants from the wastewater and industrial pollutants as well as the abundance of suspended algae. Since the water quality of Danau Kota Lake has marked some issues, the present study may assist Kuala Lumpur City Council to prevail the lake water quality challenge promptly by cost saving and in efficient manner